Reverse Phase Liquid Chromatography Coupled with Quadra pole- Time of Flight Mass Spectrometry for the Characterisation of Phenolics from Acacia catechu (L.f.) Willd - Sulaiman C. T.; Gopalakrishnan V. K; Indira Balachandran (International Journal of Phytomedicine, 2012)
A rapid method was developed for the identification of phenolics from Acacia Catechu .The analysis of phenolic compounds was carried out by reversed-phase high-performance liquid chromatography (RPHPLC) coupled to electrospray ionization-time-of-flight mass spectrometry (ESI-Q-TOF-MS). The accurate mass data for the molecular ions were processed using the software Mass Hunter work station (Agilent Technologies), which provided a list of possible elemental formulas by using the Molecular featured extraction editor. The subsequent structure characterization was carried out by a tandem mass spectrometric method. Fragmentation behavior of phenolic compounds was investigated using ion trap mass spectrometry in negative mode. The total fragmentation of the compound ion leading to other fragments was corroborated by MS–MS. Five phenolic compounds have been identified from the methanolic extract of Acacia Catechu.